ANALISIS PERAN TIM PENCEGAHAN DAN PENANGANAN KEKERASAN DALAM MENGATASI PERUNDUNGAN DI SDN 106/IX SEBAPO - Febrian; Ahmad Hariandi; Akhmad Faisal Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of the Violence Prevention and Handling Team (TPPK) in overcoming bullying at SDN 106/IX Sebapo. The background of this research is the persistent phenomenon of bullying in schools as a microsystem that requires structured intervention, in line with the mandate of Permendikbudristek No. 46 of 2023. This study uses a qualitative approach with a phenomenological type to understand the subjective experiences of school actors. Data were collected through in-depth interviews with the principal, TPPK coordinator, teachers, and students, as well as document studies. The results showed that the role of TPPK was implemented through preventive strategies (education, socialization, and student involvement) and curative strategies (restorative justice focusing on mediation). This role fundamentally shifts the handling paradigm from reactive-individual to systematic-institutional. However, there is a significant gap between policy and practice caused by structural challenges (teacher double workload and lack of counseling skills) and cultural challenges (students' fear of reporting and normalization of verbal aggression). The conclusion of this study is that the role of TPPK has succeeded in becoming a catalyst for school climate transformation, namely by building psychological safety and encouraging a shift from a culture of silence to a culture of voice